Neonatal Outcomes by Attempted Mode of Delivery and Obstetric Intervention for Pregnancies Affected by Spina Bifida [19R]. (May 2017) - Spiliopoulos, Michail; Iqbal, Sara; Reddy, Uma; Landy, Helain; Huang, Chun-Chih
Abstract : INTRODUCTION: To evaluate immediate neonatal outcomes of pregnancies affected by spina bifida by attempted vaginal delivery vs. cesarean section and spontaneous compared to induced labor. METHODS: This is a retrospective cohort study using data from the Consortium on Safe Labor study, including 228, 562 deliveries from 19 hospitals across the U.S. from 2002 to 2008. All singleton pregnancies complicated by spina bifida that resulted in a live birth after 34 weeks of gestation were evaluated. Breech deliveries were excluded from the analysis. Outcomes included NICU admission, respiratory morbidity, sepsis, birth trauma, asphyxia/seizures and mortality and were evaluated according to attempted mode of delivery and spontaneous vs induced labor. Multivariable logistic regression was used to calculate adjusted OR (aOR) and 95% confidence intervals controlling for gestational age and diabetes. RESULTS: We identified a total of 51 patients with spina bifida in the database. Women undergoing attempted vaginal delivery were more likely to be nulliparous, less than 35 years of age, white and without a history of previous cesarean delivery (CD) (p value < 0.05) compared to women undergoing planned CD. There was no statistically significant difference in immediate neonatal outcomes between patients attempting vaginal delivery and those scheduled for CD (p=0.07 for NICU admission). No differences in neonatal outcomes of pregnancies affected by spina bifida were identified between the spontaneous labor and scheduled labor induction group. CONCLUSION: Neither mode of delivery (attempted vaginal vs scheduled CD) nor scheduled induction of labor had any statistically significant impact on immediate neonatal outcomes of infants with spina bifida.